2017
DOI: 10.3390/w9070521
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Soil Moisture Estimation Using Ground Penetrating Radar in Desert Steppe

Abstract: Ground penetrating radar (GPR) is a new technique of rapid soil moisture measurement, which is an important approach to measure soil moisture at the intermediate scale. To test the applicability of GPR method for soil moisture in desert steppe, we used the common-mid point (CMP) method and fixed offset (FO) method to evaluate the influence factors and the accuracy of GPR measurement with gravimetric soil moisture measurements. The experiments showed that Topp's equation is more suitable than Roth's equation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Water resources mapping and management Glaciers mapping Landsat, ASTER GDEM, GIS, TIN 3D model. [36] Soil moisture detection GPR, CMP, FO, GIS spatial analysis [16] Groundwater and subsidence analysis GIS spatial analysis, GPS [37] Irrigation planning UAV, HTM for video image classification, GIS visualization [32] Rainfall measurements and design storm…”
Section: Application Fields Specific Contents Gis Algorithm Model mentioning
confidence: 99%
See 2 more Smart Citations
“…Water resources mapping and management Glaciers mapping Landsat, ASTER GDEM, GIS, TIN 3D model. [36] Soil moisture detection GPR, CMP, FO, GIS spatial analysis [16] Groundwater and subsidence analysis GIS spatial analysis, GPS [37] Irrigation planning UAV, HTM for video image classification, GIS visualization [32] Rainfall measurements and design storm…”
Section: Application Fields Specific Contents Gis Algorithm Model mentioning
confidence: 99%
“…The common soil moisture measurement technologies, such as the gravimetric method, neutron method, Time Domain Reflector (TDR), Frequency Domain Reflectometry (FDR), and so on, provide point measurements with high accuracy, while being labor and time-consuming and may destroy the soil structures. Lu et al [16] in this special issue present their study to measure the steppe soil moisture using Ground Penetrating Radar (GPR). The common-mid point (CMP) method and fixed offset (FO) method are used for sensitivity analysis, while the gravimetric soil moisture measurements are used to validate the accuracy of the GPR measurements.…”
Section: Water Resources Mapping and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of clay also has a large influence on the soil dielectric permittivity, which increases with the soil clay content. As the clay content increased, both the real and imaginary parts of the relative soil permittivity increased [23,26]. The reasons for the low soil dielectric permittivity at high soil clay contents are the high volume expansion, high moisture absorption capacity, and high electrical conductivity, which result in high dielectric losses.…”
Section: Effects Of Soil Properties On the Soil Dielectric Permittivitymentioning
confidence: 99%
“…Recently, ground penetrating radar (GPR) has been widely used to determine SWC at the field scale because it does not directly measure SWC; rather, it is a common practice to use fitted curves that describe the relationship between SWC and the soil dielectric permittivity [4,12]. The GPR method is rapid and continuous and provides in situ measurements of underground media; consequently, it has been applied in a variety of disciplines, such as hydrology, hydrogeology, archaeology, glacier and frozen soil research, soil science, and environmental science [5,18,[23][24][25][26]. For example, according to [4] and [27], authors reviewed four methods to measure SWC with GPR and suggested that high-frequency electromagnetic techniques are the most promising methods for measuring SWC.…”
Section: Introductionmentioning
confidence: 99%